DISTANCE LEARNING TECHNOLOGY AS A TOOL FOR COMPETITIVE GROWTH OF EDUCATIONAL PROGRAMMES IN UNIVERSITIES - K. B. Prigozhina; K. V. Trostina (Образование и наука)
Introduction. The programs of distance education are in a great demand. Therefore, the problems of the organization in higher education institutions of educational process with the use of appropriate technologies have arisen. The aim of the publication is to set an example of introducing distance learning tools into higher education system, which could help to identify possible conditions and ways of creating a virtual educational environment covering in continuity three-cycle structure of higher education, as well as non-degree supplementary educational programs. Methodology and research methods. Basic research methods include comparative analysis, qualitative and quantitative methods based on empirical observation and data processing. The methodological base for the research included competence and student-centered approaches, psycho-didactic and acmeological approaches to lifelong learning. Results and scientific novelty. The role of distance educational technologies in ensuring availability and competitiveness of programs of the basic and continuing education is emphasized. The alternative choice of creating a virtual educational environment on the basis of distance learning technologies in a non-linguistic university is proved from linguodidactic basis. The interaction of principles, approaches, and conditions for its implementation and development are given. The research provides a model of an electronic teaching complex and a two-cluster model of the coursebook as a part of virtual educational unit. Practical application of these models contributes to self-study and learning autonomy of students. Practical significance. The authors describe the content and structure of innovative teaching resources that enable to rely on student-centered approach. The recommendations on establishing a virtual educational environment in universities of programs-in-demand implementation of the basic and continuing education are provided.